(untitled) (ҚазҰУ хабаршысы. Шығыстану сериясы, 2018)
aspect is of special interest for linguistics. In some languages the number besides designation of the account of objects still has symbolical value therefore it can act in conjectural function or as a symbol of metaphysical reality, allowing to comprehend more deeply the world around and the person. ISSN 1563-0226 Journal of Oriental Studies. №1 (84). 2018 107 Considering extralinguistic factors which define national specifics of symbolics of numerical components and also the diverse system of abstract and theoretical views and figurative and sensual representations of the Kazakh people, values of number as a part of phraseological units of this language are revealed. Prospects of a research are connected with further studying of symbolics of a numerical component in phraseological units of Kazakh and their functioning taking into account national and cultural specifics.